Efficacy Of Pgf2α With Ceftiofur Sodium In Toxic Or Septic Puerperal Metritis In Dairy Cows - Kumar, Senthil; Balaji, Sri; Rani, R. Uma (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The objective of this study was to evaluate the efficacy of a systemic treatment of toxic or septic puerperal metritis in dairy cows with ceftiofur and PGF2α. Twenty crossbred cows having septic puerperal metritis 1-2 weeks postpartum were treated with PGF2α (Dinoprost triomethamine 5 mg/ ml) – Inj. Lutalyse @ 5 ml i/m on the first day followed by ceftiofur sodium @ 2.2 mg per kg i/ m for 5 days. Ringers lactate, dextrose saline and supportive multivitamin therapy for 3 days were also administered. All the observed clinical signs septic puerperal metritis came into normal after 5 days of treatment and animals recovered uneventfully.
Keywords: Toxic or septic puerperal metritis; Dairy cows; PGF2á; Ceftiofur